Improving learning ownership, digital literacy, and cognitive learning outcomes of Manokwari high school students via Kuartet biologi - Suzan Sendy Hehamahwa; Herawati Susilo; Sofia Ery Rahayu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The 21st century learning is an educational approach aimed at preparing students with relevant skills, literacy and knowledge in the digital era. The purpose of this study was to improve learning ownership, digital literacy, and students' cognitive learning outcomes through the application of the Kuartet Biologi application in learning. The method applied in this study was a quasi-experiment with a pretest-posttest non-equivalent control group design. The research sample consisted of 160 students of class XI Biology of Senior High School 2 Manokwari. Learning ownership was measured using self-assessment sheet. Students' digital literacy was measured through observation and self-assessment. Pretest and posttest were used to measure students' cognitive learning outcomes. Learning ownership and digital literacy, and students' cognitive learning outcomes were analysed using ANCOVA test. The findings showed that the use of Kuartet Biologi application affects learning ownership, digital literacy, and cognitive learning outcomes.